2010
DOI: 10.1007/s00125-010-1829-2
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal α1-antitrypsin therapy avoids fatal anaphylaxis, prevents type 1 diabetes and reverses hyperglycaemia in the NOD mouse model of the disease

Abstract: Aims/hypothesis Human α1-antitrypsin (hAAT) gene therapy prevents type 1 diabetes in a NOD mouse model of diabetes. However, repeated i.p. injections of hAAT into NOD mice leads to fatal anaphylaxis. The aim of the study was to determine if an alternative route of administration avoids anaphylaxis and allows evaluation of hAAT's potential for diabetes prevention and reversal. We also sought to determine if the addition of granulocyte colonystimulating factor (G-CSF), augments hAAT's capacity to prevent or reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
(42 reference statements)
1
32
0
Order By: Relevance
“…Islets are adversely effected by inflammatory cytokines (7). The potential attractiveness of AAT treatment to provide islet cytoprotection is enhanced by observations that short-term AAT treatment restores euglycemia and islet self-tolerance in overtly T1D NOD mice (16) as well as prevents diabetes in NOD mice (17,18). AAT is an antiprotease and it seems reasonable that this activity is central to its antiinflammatory and cytoprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Islets are adversely effected by inflammatory cytokines (7). The potential attractiveness of AAT treatment to provide islet cytoprotection is enhanced by observations that short-term AAT treatment restores euglycemia and islet self-tolerance in overtly T1D NOD mice (16) as well as prevents diabetes in NOD mice (17,18). AAT is an antiprotease and it seems reasonable that this activity is central to its antiinflammatory and cytoprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the autoimmune animal model for type 1 diabetes, the nonobese diabetic (NOD) mouse, AAT levels were half the levels found in the majority of other wildtype mouse strains (96). Indeed, preclinical data show a consistent benefit with AAT in the protection of islets and modification of immune systems across multiple models of diabetes (7,8,10,84,(96)(97)(98). Furthermore, after NOD mice revert to normoglycemia by a 14-d course of AAT, grafted autoreactive β cells are accepted in the animals in the absence of subsequent requirement for exogenous AAT (7).…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…However, it is challenging to control the progress of inflammaging. In several animal models of inflammation related diseases, hAAT has been shown to have remarkable effect on delaying or blocking the onset of diseases or alleviating the symptoms (Ma et al ., 2010; Cao et al ., 2011; Grimstein et al ., 2011; Moldthan et al ., 2014; Akbar et al ., 2016; Elshikha et al ., 2016). In fact, some of them are age‐associated diseases, such as arthritis and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that hAAT is a multifunctional protein and may play an important role in modulating the immune system. First, application of hAAT has been shown to alleviate symptoms in many disease models whereby immunity and inflammation were implicated, such as type 1 diabetes (Lu et al ., 2006; Zhang et al ., 2007; Ma et al ., 2010), islet cell transplantation (Lewis et al ., 2008), rheumatoid arthritis (Grimstein et al ., 2010, 2011), stroke (Moldthan et al ., 2014), and bone loss (Cao et al ., 2011). A recent study indicated AAT treatment inhibited instant blood‐mediated inflammatory reaction (IBMIR) and islet apoptosis after islet cell transplantation (Wang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%